BEST - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
The BEST (Belize Enterprise for Sustained Technology) is a private non-profit making organization managed and operated by Belizeans and dedicated to improving and sustaining the economic, social and cultural wellbeing of low income people of Belize....